Kinerja Motivator KB Pria terhadap Tingkat Pengetahuan dan Motivasi untuk Mengikuti Metode Operatif Pria (MOP) Bantul Tahun 2016 - Nuryani, Tuti; Widyasih, Hesty; Rahmawati, Anita (Jurnal Kesehatan Ibu dan Anak, 2017)
The existing demographical condition was a problem that needed attention and solution in a thorough, serious, and sustainable way.One of the efforts that the government has done and needed to do along with all strata of people is by controlling the number ofpopulation through the improvement of family planning service and reproduction health that affordable, qualified,and effective tocreate small family with high quality. This study was aimed at obtaining the description on the relationship of male Family Planningmotivator with the knowledge level and motivation to participate in Male Operative Methods (Vasectomy). The kind of this study wasanalytic survey by applying quantitative approach. Sample are husbands of reproductive female in Kecamatan Sanden. There were102 sample used. Analyzed the data with chi-square. The study findings that there was significant level between the performance ofmale Family Planning motivator and level of knowledges (p-value 0.019 <0,05). There was significant relationship between theperformance of male Family Planning motivator and motivation to participate in Male Operative Methods (Vasectomy) (p-value0.000<0,05).There was relationship between the performance of male Family Planning motivator to the knowledge level andmotivation to participate in Male Operative Methods (Vasectomy)